Effect of Transcutaneous Electrical Acupuncture Point Stimulation at Different Frequencies in a Rat Model of Neuropathic Pain. Issue 2 (April 2017) - Yu, Xiangdi; Zhang, Fangxiang; Chen, Bingning
Background: Acupuncture and related techniques are used worldwide to alleviate pain; however, their mechanisms of action are still not fully understood. In the present study, we investigated the effect of transcutaneous electrical acupuncture point stimulation (TEAS) at different frequencies in a chronic constriction injury (CCI) model of neuropathic pain in rats. Methods: CCI was induced by ligating the common sciatic nerve, which produced neuropathic pain. 18 male Sprague–Dawley rats with CCI were randomly divided into three groups (n=6 each) that remained untreated (CCI group) or received TEAS at high frequency (CCI+TEAS-H group) or TEAS at low frequency (CCI+TEAS-L group). Rats in the CCI+TEAS-H group received high frequency stimulation (6–9 mA, 100 Hz) at GB34/GV26/ST36; those in the CCI+TEAS-L group received low frequency stimulation (6–9 mA, 2 Hz) at the same points. Rats in the control group had the same electrodes applied but received no stimulation. All three groups were subjected to behavioural studies after treatment. Expression of μ opioid receptors (MORs) in the L3–L5 dorsal root ganglion (DRG) was determined by immunofluorescence staining and Western blotting after treatment. Results: Compared with the untreated CCI group, both mechanical allodynia and thermal hypergesia were significantly attenuated, and MOR expression in the DRG was significantly increased by low frequency TEAS treatment at GB34/GV26/ST36 (p<0.05). In contrast, no significant differences were observed between the CCI and CCI+TEAS-H groups. Conclusions: The use of low frequency TEAS significantly mitigated neuropathic pain in this rat model, and its analgesic effect is likely mediated by upregulation of MOR expression in the DRG.